The resegregation of schools : education and race in the twenty-first century - Donnor, Jamel K.; Dixson, Adrienne D. (Routledge research in education ;, 2013)
Access to a quality education remains the primary mechanism for improving one's life chances in the United States, and for children of color, a "good education" is particularly linked to their individual and collective well-being. Despite the popular perception that America is in a "post-racial" epoch, opportunities to access quality learning environments and human development resources remain determined according to race, class, gender, and ability. Taking a more nuanced approach to race and the resegregation of the American school system, this volume examines how and why the education qua